Effect of guideline based computerised decision support on decision making of multidisciplinary teams: cluster randomised trial in cardiac rehabilitation. (27th April 2009) - Goud, Rick; de Keizer, Nicolette F; ter Riet, Gerben; Wyatt, Jeremy C; Hasman, Arie; Hellemans, Irene M; Peek, Niels
Abstract : Objective To determine the extent to which computerised decision support can improve concordance of multidisciplinary teams with therapeutic decisions recommended by guidelines. Design Multicentre cluster randomised trial. Participants Multidisciplinary cardiac rehabilitation teams in Dutch centres and their cardiac rehabilitation patients. Interventions Teams received an electronic patient record system with or without additional guideline based decision support. Main outcome measures Concordance with guideline recommendations assessed for two standard rehabilitation treatments—exercise and education therapy—and for two new but evidence based rehabilitation treatments—relaxation and lifestyle change therapy; generalised estimating equations were used to account for intra-cluster correlation and were adjusted for patient's age, sex, and indication for cardiac rehabilitation and for type and volume of centre. Results Data from 21 centres, including 2787 patients, were analysed. Computerised decision support increased concordance with guideline recommended therapeutic decisions for exercise therapy by 7.9% (control 84.7%; adjusted difference 3.5%, 95% confidence 0.1% to 5.2%), for education therapy by 25.7% (control 63.9%; adjusted difference 23.7%, 15.5% to 29.4%), and for relaxation therapy by 25.5% (control 34.1%; adjusted difference 41.6%, 25.2% to 51.3%). The concordance for lifestyle change therapy increased by 3.2% (control 54.1%; adjusted difference 7.1%, −2.9% to 18.3%). Computerised decision support reduced cases of both overtreatment and undertreatment. Conclusions In a multidisciplinary team motivated to adopt a computerised decision support aid that assists in formulating guideline based care plans, computerised decision support can be effective in improving the team's concordance with guidelines. Therefore, computerised decision support may also be considered to improve implementation of guidelines in such settings. Trial registration Current Controlled Trials ISRCTN36656997 .